Effect of occlusion on joint sounds in asymptomatic individuals. - Garcia, Alício Rosalino; Zuim, Paulo Renato Junqueira [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Paulo Henrique dos [UNESP]; Ribeiro, Adriana Barbosa; Pita, Murillo Sucena; Flacón-Antenucci, Rosse M (My University, 2008)
Occlusion is a predisposing factor for Temporomandibular Dysfunctions (TMD) of the joint, whose first sign and/or symptom is usually joint sound. To verify the effect of occlusion on joint sounds, temporomandibular joints (TMJ) were analyzed in 78 asymptomatic individuals with various dental conditions. Electrosonography was used to determine the intensity of the vibration in the temporomandibular joint (TMJ) on opening and closing the mouth. Transducers (piezoelectric accelerometer) were placed on the right and left joints. Results were tabled and analyzed using the Kruskal-Wallis test (a=0.05). It was concluded that TMJ vibration in partly edentulous individuals from Kennedy classes I, II and III is statistically higher than in dentate and fully edentulous subjects.
Keywords: diagnostic agent; acceleration; adolescent; adult; age; aged; child; comparative study; edentulousness; electrodiagnosis; human; instrumentation; joint characteristics and functions; methodology; middle aged; pathophysiology; physiology; risk factor; sound; sound detection; temporomandibular joint; tooth occlusion; transducer; vibration; Acceleration; Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Child; Dental Occlusion; Electrodiagnosis; Humans; Jaw, Edentulous; Jaw, Edentulous, Partially; Middle Aged; Range of Motion, Articular; Risk Factors; Sound; Sound Spectrography; Temporomandibular Joint; Transducers; Vibration; Young Adult